Marketing Strategy in the Banking Industry Supported by Business Analysis - J R, Aneesh (Digital Repository of Theses - SSBM Geneva, 2025)
This study investigates marketing strategies within India's public, private, and cooperative banks, with a focus on assessing awareness levels, evaluating effectiveness, and identifying success or failure factors. Conducted to address the competitive demands of the banking sector, the research aims to understand how different banks leverage various marketing strategies and the integral role of business analysis and strategic planning. Utilizing a descriptive and analytical research design, data was collected from 406 respondents across different managerial levels. The analysis employed a mix of descriptive and inferential statistical techniques to ensure robust and reliable findings. The outcomes reveal significant differences in the awareness and effectiveness of marketing strategies across managerial levels and bank types. Private banks excel in using modern digital marketing techniques such as content marketing and influencer collaborations. Major reasons for marketing failures, particularly in public and cooperative banks, include a lack of clear strategy and poor market research. Additionally, private banks more frequently adopt advanced technologies like AI and big data analytics, enhancing their marketing precision and personalization. The study identifies strategic planning and business analysis as critical components for successful marketing campaigns, enabling informed decision-making, optimal resource allocation, and effective success measurement. The study’s implications highlight the necessity for regular training programs, comprehensive strategic planning, and advanced technology adoption to boost marketing effectiveness. Emphasizing the role of business analysis, these findings provide a roadmap for banks to optimize marketing strategies, improve customer engagement, and achieve better performance. By fostering a culture of data-driven decision-making and strategic foresight, banks can ensure sustained growth and competitiveness in the rapidly evolving banking sector. Keywords: Marketing Strategies, Banking Sector, Business Analysis, AI Adoption, Strategic Planning.